Innovations in small business service sector: multicase study in private schools of Sergipe - Menezes, Cassio Roberto Conceição de; Teixeira, Rivanda Meira (Revista de Administração da UFSM, 2018)
Majority of academic publications on innovation has focused on aspects of technological innovation, with orientation for the industrial sector and in smaller number on the service sector. As innovation in service is a field of studies in evolution and, therefore, requires a special attention for its apprehension, the objective of this study is to analyze innovations implemented by entrepreneurs in private schools, from the categories of innovation in service of Sundbo and Gallouj (1998) and the model of innovation of Hansen and Birkinshaw (2007). For this, the research method of multiple cases studies was adopted, and evidences was collected with three entrepreneurs of small and medium private schools size located in Sergipe, through semi structured interviews based on analytical categories from these theoretical models adopted. It was observed that these schools basically promote innovations in their process, in their organization or management and in solutions for specific problems presented by its customers. Generally speaking the changes carried through by these managers in these enterprises, can be seen as innovations only for the company or for the local market and they cannot be understood as an radical innovation.